Predictors of Mortality in Chronic Obstructive Pulmonary Disease: A Comprehensive Review (Cuestiones de Fisioterapia, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a progressive respiratory disorder characterized by persistent airflow limitation, chronic inflammation, and significant systemic manifestations. COPD remains one of the leading causes of morbidity and mortality worldwide, imposing a substantial burden on healthcare systems and negatively affecting quality of life. Despite advances in pharmacological and nonpharmacological management, mortality rates among COPD